The Relationship between the Application of Problem-Based Learning Methods and the Learning Outcomes of Computer Course Participants at Smart College Padang - Putri, Kendita; Irmawita, Irmawita (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2024)
The background to this research is the low learning outcomes of computer course participants at LKP Smart College Padang. This is thought to be due to the poor application of problem based learning methods so that the learning outcomes of course participants are low. The objectives of the research are: 1) To find out the description of the application of the Problem Based Learning method to the learning outcomes of computer course participants at LKP Smart College Padang, 2) To find out the description of the learning outcomes of computer course participants at LKPSmart College Padang, 3) To find out the relationship between the application of the method Problem Based Learning on the learning outcomes of computer course participants at LKP Smart College Padang.This type of research is correlational, with a quantitative approach. The population in this study was 30 people and a sample of 21 people whose sample was determined using the Simple Random Sampling method. Then a questionnaire is used to collect data. As well as data analysis techniques using percentage and rank order formulas.The results of the research show that: 1) The description of the application of the Problem Based Learning method among computer course participants at Smart College Padang is categorized as low; 2) A description of the learning outcomes of computer course participants at LKP Smart College Padang is categorized as low. 3) A description of the significant relationship between the application of the problem based learning method and the learning outcomes of computer course participants at LKP Smart College Padang.The research suggestions are: 1) It is hoped that instructors can innovate regarding learning methods so that they can become good and appropriate learning methods for course participants to learn. 2) It is hoped that course participants will be able to learn and adapt learning methods so that they can maximize learning outcomes. 3) It is hoped that future researchers will innovate and research new variables to add variables and complete them.